Asthma and Obesity in Children Are Independently Associated with Airway Dysanapsis - Jones, Marcus H.; Roncada, Cristian; Fernandes, Morgana Thais Carollo; Heinzmann-Filho, João Paulo; Sarria Icaza, Edgar Enrique; Mattiello, Rita; Pitrez, Paulo Marcio C.; Pinto, Leonardo A.; Stein, Renato T. (Frontiers in Pediatrics, 2017)
Background An increase in the prevalence of overweight and asthma has been observed. Both conditions affect negatively lung function in adults and children. The aim of this study was to analyze the effect of overweight and asthma on lung function in children. Methods We designed a case–control study of healthy and asthmatic subjects nested within an epidemiological asthma prevalence study in children between 8 and 16 years of age. The effect of asthma and overweight on lung function was assessed by impulse oscillometry and spirometry obtained at baseline and 10–15 min after salbutamol. Results 188 children were recruited, 114 (61%) were asthmatics and 72 (38%) were overweight or obese. Children with asthma and overweight had a higher FVC (+1.16 z scores, p < 0.001) and higher FEV1 (+0.79 z scores, p = 0.004) and lower FEV1/FVC (−0.54 z scores, p = 0.008) when compared to healthy controls. Compared to normal weight asthmatics, the overweight had higher FVC (+0.78 z scores, p = 0.005) and lower FEV1/FVC (−0.50 z scores, p = 0.007). In the multivariate analysis, overweight was associated with an increase of 0.71 and 0.44 z scores in FVC and FEV1, respectively, and a reduction in FEV1/FVC by 0.40 z scores (p < 0.01 for all). Overweight had no effect on maximal flows and airway resistance at baseline, and this was not modified by inhalation of a bronchodilator. Asthma was also associated with higher post-BD FVC (0.45 z scores, p = 0.012) and FEV1 (0.35 z scores, p = 0.034) but not with FEV1/FVC and FEF25–75%. Two-way analysis of variance did not detect any interaction between asthma and overweight on lung function variables before or after bronchodilator. Conclusion Our results suggest that asthma and overweight are independently associated with airway dysanaptic growth in children which can be further scrutinized using impulse oscillometry. Overweight contributed more to the reduction in FEV1/FVC than asthma in children without increasing airway resistance. Spirometry specificity and sensitivity for obstructive diseases may be reduced in populations with high prevalence of overweight. Adding impedance oscillometry to spirometry improves our understanding of the ventilatory abnormalities in overweight children.